PENGARUH MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. WAJA MOTOR CABANG SUKAWATI - I Ketut Agus Suweca; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
Work productivity is defined as a concrete result (product) produced by individuals or groups, during a certain unit of time in a work process. In order for employees to be productive at work, an organization or company needs to pay attention to the factors that affect employee productivity. The purpose of this study was to determine the effect of work motivation and work experience on employee work productivity at CV. Waja Motor Sukawati Branch. This research was conducted on CV. Waja Motor Sukawati Branch. The number of samples taken as many as 30 employees using saturated samples. Data was collected by means of interviews, documentation, observation and distributing questionnaires. The research instrument used is validity test and reliability test. The analytical technique used is the classical assumption test, multiple correlation test, analysis of determination, multiple linear regression analysis, F test and t test. Based on the results of the analysis obtained that work motivation has a positive and significant effect on employee work productivity at CV. Waja Motor Sukawati Branch. work experience has a positive and significant effect on employee work productivity on CV. Waja Motor Sukawati Branch. Determination is obtained from the amount of R Square in Table 5.11 which is 0.701 or 70.10%. Determination of 70.10%, meaning that the variable of Work Motivation (X1) and the variable of Work Experience (X2) is able to explain the variable of Employee Work Productivity (Y) is 70.10%. The remaining 29.90% (100% - 70.10%) was explained by other factors not included in this study.